A Shield Does Not Fall in Hazelwood: Privileging the Legitimate Journalism of High School Student Reporters - Hu, June M. (The Columbia Journal of Law & the Arts, 2015)
After fifteen-year-old Audrie Pott hanged herself, student reporters on her high school’s newspaper began investigating the circumstances leading up to the tragedy. The newspaper staff at Saratoga High School conducted over fifty interviews regarding Audrie’s sexual assault and the photos of her attack that classmates had circulated before her suicide. After weeks of research, three reporters published their findings on April 14, 2013, in an article involving five anonymous student sources. In August, when the three student reporters went back to school for the first day of a new academic year, they found subpoenas waiting for them. The subpoenas required them to name the confidential sources in their article. The reporters chose to protect the names of their confidential student sources, for whom exposure could carry harsh social, disciplinary and legal ramifications.